N.P. van Wyk Louw and R.A.F. [i.e. R.F.A.] Hoernlé: Notes on liberal and nationalist discourse in South Africa, 1939-1955 - Olivier, Gerrit (My University, 1994)
The contribution of the poet N.P. van Wyk Louw (1906-1970) to the debate on Afrikaans literature, politics and cultural life has been seminal in many respects. Although different aspects of Louw's thought need to be viewed as a whole in order to understand what I wish to call his "cultural project", his writings on nationalism will be the focus of this paper, which I wish to present as a minor contribution to the history of ideas in South Africa.… My paper will be ordered along the following lines. First, I will analyse "Vegparty of polemiek?", the first clear example of Louw's new approach to nationalism and South African politics, exposing the striking similarities between the analysis Hoernle gave in 1939 and Louw's views on the role of political discussion in bringing about a rapprochement between liberalism and nationalism. This is followed by an analysis of similarities between Hoernle's philosophical stance and Louw's intellectual claims. Next, I will discuss various aspects of Louw's later essays on national ism in order to illustrate that Louw's new interpretation of nationalism can be understood as a conscious parallel to Hoernle's contribution to the South African debate on liberalism. Finally, I will analyse the practical problems raised by both writers, showing how Louw's philosophical stance produced a dilemma that is more satisfactorily resolved in Hoernle.
African Studies Seminar series. Paper presented 30 May 1994
Keywords: Louw, N. P. van Wyk, 1906-1970. Political and social views; Hoernlé, Reinhold Friedrich Alfred, 1880-1943. Political and social views; South Africa. Intellectual life. 20th century